Endoscopic Management of Iatrogenic Colon Perforation - Yunho Jung (Korean Society of Gastrointestinal Endoscopy, 2020)
Colon perforations are difficult to resolve because they occur unexpectedly and infrequently. If the clinician is unprepared or lacks training in dealing with perforations, the clinical prognosis will be affected, which can lead to legal issues. We describe here the proper approach to the management of perforations, including deciding on endoscopic or surgical treatment, selection of endoscopic devices, endoscopic closure procedures, and general management of perforations that occur during diagnostic or therapeutic colonoscopy.